Promising Futures: CMS, Post‐Disciplinarity, and the New Public Social Science. (18th September 2013) - Delbridge, Rick
Abstract This paper considers the future prospects for Critical Management Studies and by extension management studies more generally. To explore these, two frameworks from the wider social sciences are deployed. The anchorpoint for the discussion is Michael Burawoy's work distinguishing types of scholarship on the bases of (a) conceptions of knowledge produced by social scientists, and (b) different audiences for that knowledge. Critical Management Studies is founded on critique but its future will be determined by how it makes its way across Burawoy's other domains of professional, policy and public scholarship. To examine this, I draw on John Brewer's recent articulation of the 'new public social science'. Brewer's problem‐driven, post‐disciplinary approach conceives the public value of social science as its conservation of moral sentiments and sympathetic imagination towards each other as social beings, and its ethical concern about the humanitarian future of humankind. The new public social science is normative and partisan, transgressive, scientific, and impactful. I argue that this provides a potentially fruitful template to guide future management studies. This is a future in which Critical Management Studies – as management studies' critical and emancipatory conscience – has a central role to play.